Republic of Mozambique : Staff Report for the 2005 Article IV Consultation, Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Performance Criteria, and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2005)
This paper highlights Mozambique's 2005 Article IV Consultation, Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), Request for Waiver of Performance Criteria, and Modification of Performance Criteria. The performance under the program supported by the PRGF was mixed during October 2004-March 2005. All end-December 2004 quantitative performance criteria, except the one pertaining to the fiscal deficit, were met. Prospects for 2005 remain favorable, including for strong growth, a further deceleration in inflation, and maintenance of a sustainable external position.